THE USE OF TASK-BASED LANGUAGE TEACHING IN THE SPEAKING CLASS IN IMPROVING STUDENTS’ CRITICAL THINKING - Nidia Trisnawati (Journal of English Education Program (JEEP), 2018)
This paper reports on the implementation of task-based language teaching in improving students’ critical thinking. This study was aimed at figuring out the implementation of task-based language teaching in the speaking class by the lecturer in improving students’ critical thinking. This study was conducted because the writers realize that critical thinking is very important for the students. Therefore, to improve students’ critical thinking the lecturer has to provide suitable approach to make teaching and learning process more optimal. This study employed a qualitative research that was designed as a case study design. The finding revealed that based on the observation result, the lecturer used task-based language teaching in three stages among others is pre-task stage, task-cycle stage, and post-task stage. It is supported by the result of interview which showed that task can help the students in understanding the material; hence they can improve their critical thinking when they conducted a classroom discussion. Then, based on the findings of questionnaire, the students’ perceptions on the use of task-based language teaching are very positive because most of the students’ enjoy and interested in the teaching and learning process by using task-based language teaching. Therefore, it can be concluded that the use of task-based language teaching is very useful for the students.